Constructing Meaning in Learning Containing the Living Environment - R Wuryaningrum; F Aziz (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
This research aims to describe the teacher's explanation in constructing the meaning of learning containing the living environment in Indonesia. This research uses descriptive explanatory method. The research was conducted by observing and analyzing classroom learning discourse in elementary schools labeled Adiwiyata or school whose learning is related to the living environment education. The results of the study show that the teacher's explanation contains an explanation of the object, concepts, and procedures; the explanatory strategy used by the teacher is a knowledge-transforming with a reference to the social and cultural context of the society that consists of (1) religiosity (2) dependence between humans and the environment, (3) human values to preserve nature, (4) social and cultural ethics as basic human characteristics. Verbal or linguistic strategies show the teacher's awareness in using language with metaphors and expressions to motivate. Through a verbal strategy it is known that the teacher's explanation is done efferently and aesthetically. The teacher's explanation constructs the meaning of descriptive and procedural knowledge. Descriptive knowledge is knowledge that makes the learner knows or understands. Procedural knowledge makes the learner is able to. The role of teacher explanation is supported by the government's active role in environmental sustainability programs.